2021
DOI: 10.1002/esp.5075
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate on landscape form, sediment transfer and the sedimentary record

Abstract: The relationship between climate, landscape connectivity and sediment export from mountain ranges is key to understanding the propagation of erosion signals downstream into sedimentary basins. We explore the role of connectivity in modulating the composition of sediment exported from the Frontal Cordillera of the southcentral Argentine Andes by comparing three adjacent and apparently similar semiglaciated catchment-fan systems within the context of an along-strike precipitation gradient. We first identify that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 108 publications
0
13
0
Order By: Relevance
“…On land, sediment can be stored on hillslopes due to reduced hillslope-channel connectivity (Figure 5; DiBiase and Lamb, 2013;Hoffmann, 2015;Harries et al, 2021) and within the river system. Overbank flow, as well as lateral and vertical movement of the active channel can result in long-term sediment incorporation in floodplains (Nakamura and Kikuchi, 1996;Wittmann et al, 2011Wittmann et al, , 2020Bradley and Tucker, 2013;Coulthard and Van De Wiel, 2013), alluvial fans (Jolivet et al, 2014;D'Arcy et al, 2015D'Arcy et al, , 2017Guerit et al, 2016;Mason and Romans, 2018;Carretier et al, 2020), fluvial terraces (Blöthe and Korup, 2013;Limaye and Lamb, 2016;Schildgen et al, 2016;Malatesta et al, 2017Malatesta et al, , 2018Tofelde et al, 2017;Quick et al, 2019), or entire valley fills (Hilley and Strecker, 2005).…”
Section: Probability Of Transient Storagementioning
confidence: 99%
“…On land, sediment can be stored on hillslopes due to reduced hillslope-channel connectivity (Figure 5; DiBiase and Lamb, 2013;Hoffmann, 2015;Harries et al, 2021) and within the river system. Overbank flow, as well as lateral and vertical movement of the active channel can result in long-term sediment incorporation in floodplains (Nakamura and Kikuchi, 1996;Wittmann et al, 2011Wittmann et al, , 2020Bradley and Tucker, 2013;Coulthard and Van De Wiel, 2013), alluvial fans (Jolivet et al, 2014;D'Arcy et al, 2015D'Arcy et al, , 2017Guerit et al, 2016;Mason and Romans, 2018;Carretier et al, 2020), fluvial terraces (Blöthe and Korup, 2013;Limaye and Lamb, 2016;Schildgen et al, 2016;Malatesta et al, 2017Malatesta et al, , 2018Tofelde et al, 2017;Quick et al, 2019), or entire valley fills (Hilley and Strecker, 2005).…”
Section: Probability Of Transient Storagementioning
confidence: 99%
“…Differences in connectivity, lithology, and channel steepness as drivers of downstream grain‐size changes are supported by others (Attal & Lavé, 2006; Attal et al., 2015; Harries et al., 2021; Mueller & Pitlick, 2005), and these relationships are complex, leading to local coarsening and fining trends. For instance, as opposed to this study, Attal et al.…”
Section: Discussionmentioning
confidence: 74%
“…Differences in connectivity, lithology, and channel steepness as drivers of downstream grain-size changes are supported by others (Attal & Lavé, 2006;Attal et al, 2015;Harries et al, 2021;Mueller & Pitlick, 2005), and these relationships are complex, leading to local coarsening and fining trends. For instance, as opposed to this study, Attal et al (2015) found that the 50th percentile (D50 in their study) in the Feather River basin increased faster with increasing stream power compared with the maximum grain size (D100).…”
Section: Purinton and Bookhagenmentioning
confidence: 82%
“…(2018) and Harries et al. (2020), using Fick and Hijmans (2017)'s data set for precipitation patterns. Because our study focuses on disentangling the signals of tectonics from lithology, we detail this process in the supporting materials.…”
Section: Methodsmentioning
confidence: 99%